2011
DOI: 10.1017/jfm.2011.459
|View full text |Cite
|
Sign up to set email alerts
|

Binary collisions of drops of immiscible liquids

Abstract: International audienceThis experimental and theoretical study is devoted to the investigation of head-on collisions of two drops of immiscible liquids. In the experiments, pairs of drops are made to collide at well-defined kinetic and geometric conditions. The sizes and relative velocity of the colliding drops close to the point of impact are measured by means of image processing. The deformed states after the impact, their evolution with time, and their stability are studied by visualization. The theory consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…In principle, values of A slightly different from 1 are also possible. However, as pointed out by Roisman et al, 26 these would lead to solutions where f (ξ) rapidly diverges from unity as ξ increases.…”
Section: A Description Of the Flow In The Lamellamentioning
confidence: 92%
See 2 more Smart Citations
“…In principle, values of A slightly different from 1 are also possible. However, as pointed out by Roisman et al, 26 these would lead to solutions where f (ξ) rapidly diverges from unity as ξ increases.…”
Section: A Description Of the Flow In The Lamellamentioning
confidence: 92%
“…The general solution of this non-linear ODE is given by Eq. (4.10) in Roisman et al 26 As ξ approaches 0 (i.e., for large times and small radii), the function f (ξ) tends toward the integration constant A and the radial velocity in the sheet can be expressed as the asymptotic solution,…”
Section: A Description Of the Flow In The Lamellamentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies focused on the crown dynamics and droplet ejection in axisymmetric configurations [33][34][35][36][37]. Increasing attention has also been paid to impacts on small solid targets of size comparable to that of the drop diameter [38][39][40][41][42] or binary drop collision [43,44]. In the crescent-moon impact scenario, an intrinsic horizontal asymmetry leads to a nonaxisymmetric liquid sheet [19].…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of the recent theoretical and experimental results for the collisions of liquid droplets [74][75][76] together with the BUU [64] and nuclear fluid dynamics (NFD) [40] results for HIC, it is suggested that there should be four distinct stages of the collision [ Fig. 11].…”
Section: Exotic Topologies In the Intermediate Energy Collisions Hydmentioning
confidence: 99%